Implementation of Regional Government Information System Policy (SIPD) in Yapen Islands Regency: Using Van Meter and Van Horn Models - Rosalyn Gracya; Lilik Purwanti (Indonesian Scientific Publication, 2026)
The Regional Government Information System (SIPD) is an integrated electronic platform designed to support local governments in managing and disseminating information on regional development, public finance and other administrative functions. In the Yapen Islands Regency, SIPD is expected to strengthen transparency, accountability, and efficiency as part of the national goals to advance governance practices. However, the implementation of SIPD in the regency has not yet reached its optimal performance, as various technical and organizational challenges persist. This study aims to analyze the meaning and dynamics of SIPD policy implementation within the context of the Yapen Islands Regency; using the Van Meter and Van Horn model as an analytical lens with descriptive qualitative method. This model provides more comprehensive understanding of implementation processes through six interrelated dimensions: policy standards, resources, communication, implementing attitudes, organizational characteristics, and external conditions. The finding indicate that the SIPD policy implementation has been implemented but is still constrained. However, several obstacles remain, particularly unstable internet connectivity, limited technical capacity, and delay in system synchronization. These challenges are mitigated by strong local organizational culture, assertive communications among implementers, and effective cross-agency collaboration. This study supports policy-making institutions in designing SIPD, thereby enabling comprehensive development of SIPD within the public sector; considers policy standards and objectives, formulates more contextual and realistic guidelines, strengthens vertical coordination mechanisms, and facilitates more rapid technical support.